The Impact of Green Finance Policy on Investment Behavior at Renewable Energy Companies in Indonesia - Ikayanti Puspaning Kartini; Grasia Wieke Tantyasari; Mita Sonaria (Publikasi Indonesia, 2026)
This research examines the influence of Green Finance Policy on investment behavior in renewable energy companies in Indonesia. This issue is motivated by the increasing urgency of transitioning to a low-carbon economy, the substantial financing requirements for renewable energy projects, and the uncertainty regarding the effectiveness of green finance implementation in developing countries. This research aims to analyze whether Green Finance Policy influences companies’ investment behavior and whether profitability and leverage moderate this relationship. Using an explanatory quantitative approach, this study employs panel data from energy sector companies listed on the Indonesia Stock Exchange during the 2020–2024 period, with investment behavior measured using the ratio of capital expenditure to total assets. The empirical analysis was conducted using the Fixed Effects Model. The results show that Green Finance Policy has a positive but statistically insignificant effect on investment behavior. Profitability demonstrates a significant direct relationship with investment behavior but does not moderate the effect of Green Finance Policy. Leverage and firm size were also found to have insignificant effects. This study concludes that green finance policies have not yet directly encouraged renewable energy investment in Indonesia. This research contributes to the sustainable finance literature by emphasizing the importance of corporate fundamentals and macroeconomic conditions in explaining corporate investment behavior in developing countries.